Peran Pupuk Organik Terhadap Produktivitas Primer Dan Biomassa Ikan Nila (Oreochromis Niloticus) - Gulo, Lestari Purnama Intan (Jurnal Perikanan dan Kelautan, 2025)
This study examines the effect of using organic fertilizers on the level of primary productivity and biomass growth of tilapia (Oreochromis niloticus) in aquaculture systems. Organic fertilizers play a role in increasing the fertility of aquaculture media by improving the physical, chemical, and biological properties of the environment. Consistent application of organic fertilizers can increase the availability of nutrients, improve the structure of the pond bottom, and stimulate the growth of phytoplankton and zooplankton which become natural food for tilapia, thereby increasing the primary productivity of waters. This increase in primary productivity directly supports the growth and increase in biomass of tilapia. Various studies have shown that the application of organic fertilizers, both in solid and liquid form, can increase the growth rate, survival rate, and biomass yield of tilapia, although its effectiveness depends on the dosage and environmental conditions. Therefore, the use of organic fertilizers in tilapia farming not only helps to preserve the aquatic ecosystem, but also increases the overall productivity and efficiency of the tilapia farming business.